The effect of board of directors and audit committee effectiveness on internet financial reporting: Evidence from gulf co-operation council countries. Issue 4 (7th November 2016) - Bin-Ghanem, Hasan; Ariff, Akmalia M.
Abstract : Purpose: The purpose of this paper is to examine the effect of board of directors and audit committee effectiveness on the level of internet financial reporting (IFR) disclosure practices. Design/methodology/approach: The sample consists of 152 listed financial companies in Gulf Cooperation Council (GCC) countries. Based on agency theory, the authors posit that board of directors and audit committee effectiveness influence corporate IFR disclosure practice. Content analysis approach, based on an un-weighted index of 35 IFR items is used to measure the level of IFR disclosure. Thus, multiple regression analysis is utilized to analyse the results of this paper. Findings: The results show that board of directors and audit committee effectiveness has significant influence on the level of IFR disclosure. Research limitations/implications: One potential limitation of this paper is that the sample is drawn only from the GCC listed financial companies. Therefore, the findings cannot be generalized to other than the financial institutions. Practical implications: The finding(s) highlights the importance of board of directors and audit committee characteristics in corporate governance and in the development of financial markets that foster IFR disclosure. Originality/value: This paper extends previous IFR disclosure studies by considering both the role of board of directors and audit committee effectiveness score in examining IFR disclosure.